Incidence of Dry Socket after Extraction Done in Private College and Hospital-A Retrospective Study - J.S Thaslima Nandhini1 , Pratibha Ramani2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Dry socket is a most commonly seen complication of extraction. Dry socket is also known as fibrinolyticosteitis. It is an inflammation of the alveolar bone around the extracted tooth and characterized by severepain, breakdown of clot formed in the socket results in the socket empty. The main causes of dry socketis due to increased local fibrinolysis which leads to breakdown of clot. The aim of the present study is toevaluate the incidence of dry socket after extraction done in private college and hospital. We reviewedpatient records and analysed the data of 86000 patients between June 2019 and March 2020. In that, a totalof 1300 patients performed extraction. Out of the total population 0.5% has a complaint of dry socket. Thestudy was done in a private dental college and hospital. Data envy about dry socket. Excel tabulation is doneand statistics is done using SPSS software. Approval of the ethical committee was taken before the start ofthe study. A total of 1300 extractions were done in private dental college and hospital. The overall frequencyof dry socket was 0.5%. Incidence of dry socket among females(50%) is higher than the male (44.4%).Incidence of dry socket with smoking is more than non-smoking. Patients age, gender, reason for extraction,onset of symptoms, tooth number, and treatment given play no role in the occurrence of dry socket. Surgicaltrauma and smoking are the major factors in the occurrence of dry socket. High incidence of dry socketis seen in mandibular molars than the maxillary molars. Treatment with zinc oxide eugenol dressing andirrigation of socket is the most common dry socket management technique. Thus the incidence of dry socketafter extraction done in private college and hospital is estimated.